Ring Opening Polymerization of DL-Lactide Using A Supramolecular Sulfonamide – Tertiary Amine Organocatalytic System (The All Results Journal, 2012)
Sulfonamides are usual ligands for organometallic catalysis in the Ring Opening Polymerization (ROP) of cyclic esters. In our quest for original Hydrogen-bonding catalytic systems, our goal was to use a sulfonamide derivative as an electrophilic activator of DL-lactide in partnership with a tertiary amine, as a nucleophilic activator of the initiator and growing polymer chain. Several sulfonamides were synthesized and tested in the ROP of DL-lactide. The impact of sulfonamide substituents was analyzed to better understand the H-bonds involved in the process.